Synthesis of the compact low pass filter using dumbbell-shaped slot resonators - Комаров, В.Ф.; Рассохина, Ю.В.; Крыжановский, В.Г. (Radiotekhnika, 2019)
The design of the low pass filter using dumbbell-shaped slot resonators placed in the grounding layer of the microstrip transmission line was considered. Dependences of the transmission coefficient and the input impedance hodograph were investigated; the aim was to obtain a wide stop band and the required impedance on the harmonics of the operating frequency. Suppression was obtained experimentally from the second to fourth harmonic of the fundamental frequency at the level of more than 20 dB and 30 dB for prototypes. The input impedance varies from values close to infinity on even harmonics to close to zero on the odd harmonics. The proposed design can be used in microwave high efficiency power amplifiers.